Translation Techniques in Translated Commercial Break Advertisement (Proceedings of English Linguistics and Literature, 2022)
In this free trade era, one product can be freely exported or imported to another country. The problem is how to promote a product nonetheless is by providing its advertisement. Meanwhile, the advertisements used need to deliver messages which relevant to the people in the target country. This research aim was to describe a unique phenomenon in a translated advertisement. This research started by analyzing translated advertisements and their relation to translation techniques. The method used in this research was descriptive qualitative. The source of data was two advertisements of Oreo in commercial break videos. One used English, and the other used Bahasa Indonesia. In addition, the video is the same. Based on the research results, several sentences were identified using more than one technique. Based on the techniques used, literal translation and borrowing techniques were used in both videos. Furthermore, the reduction was the most technique used. In conclusion, a translated advertisement tends to keep its original text to perceive its meaning. In addition, the translated version is also influenced by the sound and image of the video. For further research, it is suggested to implement transcreation and use broader or more varied data.